Understanding the mechanisms of drug resistance in enhancing rapid molecular detection of drug resistance in Mycobacterium tuberculosis - Johnson, Rabia (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Biomedical Sciences. Molecular Biology and Human Genetics))--University of Stellenbosch, 2007.